Electrophysiological properties of vestibular hair cells isolated from human crista - Nesrien Mohamed; Mohammad Al-Amin; Frances L. Meredith; Olivia Kalmanson; Anna Dondzillo; Stephen Cass; Samuel Gubbels; Katherine J. Rennie (Frontiers in Neurology)
IntroductionThe vast majority of cellular studies on mammalian vestibular hair cells have been carried out in rodent models due in part to the inaccessibility of human inner ear organs and reports describing electrophysiological recordings from human inner ear sensory hair cells are scarce. Here, we obtained freshly harvested vestibular neuroepithelia from adult translabyrinthine surgical patients to obtain electrophysiological recordings from human hair cells.MethodsWhole cell patch clamp recordings were performed on hair cells mechanically isolated from human cristae to characterize voltage-dependent and pharmacological properties of membrane currents. Hair cells were classified as type I or type II according to morphological characteristics and/or their electrophysiological properties.ResultsType I hair cells exhibited low voltage-activated K+ currents (IKLV) at membrane potentials around the mean resting membrane potential (-63 mV) and large slowly activating outward K+ currents in response to depolarizing voltage steps. Recordings from type II hair cells revealed delayed rectifier type outward K+ currents that activated above the average resting potential of -55 mV and often showed some inactivation at more depolarized potentials. Perfusion with the K+ channel blocker 4-aminopyridine (1 mM) substantially reduced outward current in both hair cell types. Additionally, extracellular application of 8-bromo-cGMP inhibited IKLV in human crista type I hair cells suggesting modulation via a nitric oxide/cGMP mechanism. A slow hyperpolarization-activated current (Ih) was observed in some hair cells in response to membrane hyperpolarization below -100 mV.DiscussionIn summary, whole cell recordings from isolated human hair cells revealed ionic currents that strongly resemble mature current phenotypes previously described in hair cells from rodent vestibular epithelia. Rapid access to surgically obtained adult human vestibular neuroepithelia allows translational studies crucial for improved understanding of human peripheral vestibular function.